50 Video debriefing -- a research project on communication between technician and debriefer. (17th November 2016) - Gay, Christopher; Graby, M; Riby, S; Raina, A; Charlton, O; Jaworskagrajek, M
Abstract : Background/context: Video Debriefing is widely used in simulation, yet evidence has yet to be found proving its use benefits the learning. AT HILS we have noticed a wide variation in its perceived effective use. We decided to use a mandatory training day with 6 scenarios (Foundation Acute Clinical Emergencies Simulation) which occurred 15 times over a 3 month period to study the best way to assist a debriefer with video feedback. Methodology: Our video debriefing system uses digital bookmarks to highlight possible areas of interest for replay. We recorded the method in which the debriefer asked the technician to play the bookmark (ie timecode, name of bookmark or number) and the success of that interaction. We asked faculty to fill in pre and post course questionnaires on their video debriefing experience, confidence and perceived usefulness of this method. We also recorded a range of data to help analysis such as which of 4 technicians was supporting, the specific scenario, the specific debriefer, number of bookmarks recorded and used. Results/outcomes (anticipated or recorded to date): Our results showed that naming the bookmark by timecode was the most popular method of communicating as well as the most effective. We were also able to draw conclusions That there was no correlation between the number of bookmarks made and actual used to play back video All faculty showed increases in their confidence and perceived usefulness of video debriefing across the duration of the course. Potential impact: Our findings have led to A standardised method of supporting video debriefing The production of an induction session for video debriefers Increased confidence in faculty to perform video debriefing